Out of the ocean: the timescale of molluscan evolution based on phylogenomics revealed the ages of mollusks’ evolutionary transitions into the novel environment - Han, Xiaolu; Sun, Shaolei; Wang, Yiting; Liu, Mengyuan; Shui, Bonian; Han, Zhiqiang (Frontiers in Ecology and Evolution, 2024)
Being the phylum with the second largest biodiversity, mollusks are widely distributed in marine, freshwater, and land, conquered almost all habitats on the earth. Throughout geological time, several molluscan lineages independently colonized freshwater and land, evolving independently in new habitats. Resolving the timing of their colonization for novel environments is the basis of understanding the complex evolution of Mollusca. Herein, we obtained an elaborate single-copy orthologs set including 107 genes with a total length of 3,447,675 amino acid sites across 134 mollusks to reconstruct the phylogeny of Mollusca. The phylogenetic analysis recovered the "Aculifera+ Conchifera" topology with well-supported. By the divergence times estimation with fossil calibration, we revealed Cambrian rapid diversification of all molluscan classes. What's more, our results provided the times of three major independent colonization of novel environments and consistent with previous studies. The freshwater mussels (Bivalvia: Unionida) colonized freshwater about 233 Mya, ancient origin and late diversification make this order to become the main represent of the freshwater bivalves. The orders Stylommatophora and Basommatophora (Gastropoda: Pulmonata) respectively colonized land and freshwater about 201 Mya, the Triassic-Jurassic mass extinction may have provided the opportunities for their colonization. Ampullariidae (Gastropoda) colonized freshwater about 156 Mya, their lungs may have contributed to the adaption of tropical freshwater environment and make them survive. Our results probably offer the most comprehensive time-scale of molluscan evolution, could provide some insights into the habitat transition and evolution of Mollusca.